The Impact of Augmented Reality (AR) Experiences on Consumer Purchasing Behaviour w.r.t Amazon (International Journal of Food and Nutritional Sciences, 2022)
This study analyses the impact of augmented reality (AR) experiences on consumer purchasing behaviour, focusing on three key dimensions: product visualization, interactivity, and perceived value versus novelty. The primary objectives were to assess and compare these influences between Amazon users with AR features and consumers on other platforms lacking AR functionalities. The research utilized a structured methodology involving a primary survey targeting E-commerce customers of Amazon and smaller platforms. Selective sampling was employed, with 20 participants experiencing AR features on Amazon and 20 from platforms without AR. Independent Sample t-tests were applied to analyse Likelihood of Purchase based on the three identified aspects.The results revealed noteworthy findings across the dimensions studied. In the case of AR product visualization, Amazon users exhibited a significantly higher likelihood of purchase compared to those on other platforms without AR. Similarly, AR interactivity played a crucial role, with Amazon users showing both a higher likelihood of purchase and greater consistency in responses. The perceived value versus novelty of AR experiences, however, exhibited a contrasting result, with Amazon users having a lower mean likelihood of purchase and greater variability in responses compared to other platforms without AR.Based on these findings, several recommendations are proposed for optimizing the impact of AR on consumer purchasing behaviour. These include optimizing AR product visualization on Amazon, enhancing AR interactivity features, fine-tuning perceived value and novelty aspects, investing in user education and communication, regular monitoring, iteration, and expanding AR support to new product categories. Collaboration with brands for AR integration is also recommended to enrich the overall shopping experience.